2011
DOI: 10.1097/nnd.0b013e3182371190
|View full text |Cite
|
Sign up to set email alerts
|

A Taste of Nursing Research

Abstract: Developing and implementing a program to introduce clinical nurses to research and evidence-based practice (EBP) should spark interest and participation. In this article, the authors describe and evaluate a staff development initiative not only to introduce the principles of EBP and research but also to give nurses the opportunity to participate in the research process and development of EBP questions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…Of the articles reviewed, only five characterized the level of education of nurses involved in the reports (Brewer, Brewer, & Schultz, 2009;Brown, Johnson, & Appling, 2011;Clifford & Murray, 2001;Jamerson, Fish, & Frandsen, 2011;Wiener, Chacko, Brown, Cron, & Cohen, 2009). Nursing education varied, but most nurses had a diploma, associate degree, or bachelor of science in nursing (Brewer et al, 2009;Brown et al, 2011;Clifford & Murray, 2001;Jamerson et al, 2011;Wiener et al, 2009). Findings were grouped into five major themes: access to infrastructure, leadership support, strategic priorities and relevant interests, educational tactics, and leveraging established networks and resources ( Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the articles reviewed, only five characterized the level of education of nurses involved in the reports (Brewer, Brewer, & Schultz, 2009;Brown, Johnson, & Appling, 2011;Clifford & Murray, 2001;Jamerson, Fish, & Frandsen, 2011;Wiener, Chacko, Brown, Cron, & Cohen, 2009). Nursing education varied, but most nurses had a diploma, associate degree, or bachelor of science in nursing (Brewer et al, 2009;Brown et al, 2011;Clifford & Murray, 2001;Jamerson et al, 2011;Wiener et al, 2009). Findings were grouped into five major themes: access to infrastructure, leadership support, strategic priorities and relevant interests, educational tactics, and leveraging established networks and resources ( Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…While it is important for nursing research to be connected with the greater organizational research activities in order to have a successful program of nursing research (Patterson Kelly et al, 2013), it is also important to establish that research topics are relevant to patient care (Brown et al, 2011;Clifford & Murray, 2001). Relating research topics to patient care ensures that clinical staff are enthusiastic about the work and stay invested in the study.…”
Section: Strategic Priorities and Relevant Interestsmentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, there is not a clear delineation of a comprehensive training intervention to prepare nurses in clinical settings to incorporate research and EBP into practice to improve patient outcomes. It was suggested that availability of trained EBP mentors are valuable to sustain EBP (Balakas et al., ; Black et al., ; Brown et al., ; Green et al., ; Kinney et al., ; Levin et al., ; Magers, ; Muller et al., ; Rutledge & Skelton, ; Wintersgill & Wheeler, ; Yackel et al., ). Therefore, we developed a multifaceted program to identify and train EBP mentors, create online resources, and develop a formal educational program to prepare nurses to incorporate research and EBP into clinical practice.…”
Section: Introductionmentioning
confidence: 99%